ANALYSIS SATISFACTION LEVELS COLLEGE STUDENTS ON INFRASTRUCTURE IN SCIENCE AND TECHNOLOGY BUILDING UINFAS BENGKULU IN SUPPORTING LEARNING PROCESS - Apriliani Mersa Putri; Indah Lestari; Siti Sarifah Hasibuan; Tias Dwi Septianingrum; Adrian Topano (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
Mobile and immovable educational facilities and infrastructure are very important for the teaching and learning process and enable the completion of educational goals in an orderly, efficient, effective and timely manner. The learning process is an activity in which there is interaction between educators and students as well as reciprocal communication that takes place to achieve learning objectives. Factors that can influence the learning process to be effective and efficient, such as teacher, student, facilities and infrastructure as well as environmental factors. The method used in this research is descriptive analysis method. The purpose of this study was to determine the level of student satisfaction with facilities and infrastructure in one of the study programs at Fatmawati Sukarno Bengkulu State Islamic University in supporting the learning process. From the results of student satisfaction with the facilities and infrastructure to support the learning process, namely for classrooms, chairs, tables and blackboards, they stated that they were 100% satisfied. Laboratories 86% satisfied and 14% unsatisfied, for prayer rooms 70% satisfied and 30% unsatisfied. Trash box 44% satisfied and 56% dissatisfied, toilet 98% satisfied and 2% dissatisfied, projector 34% satisfied and 66% dissatisfied, fan 88% satisfied and 12% unsatisfied.